2006
DOI: 10.1158/1078-0432.ccr-05-2291
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of c-ErbB1/Epidermal Growth Factor Receptor and c-ErbB2/HER-2 Expression in Bronchial Dysplasia: Evaluation of Potential Targets for Chemoprevention of Lung Cancer

Abstract: Purpose: Lung cancer is preceded by a premalignant phase during which intervention could decrease associated morbidity and mortality. Molecular characterization of factors involved in controlling progression of bronchial dysplasias will provide markers of premalignant change and identify targets for chemoprevention. Experimental Design: Immunohistochemical analysis of epidermal growth factor receptor (EGFR; c-ErbB1/EGFR), HER-2/neu (c-ErbB2/HER-2), Ki-67, and minichromosome maintenance protein 2 (MCM2) express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
51
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(54 citation statements)
references
References 35 publications
2
51
0
1
Order By: Relevance
“…The same study reported that a high copy number correlated with a poor prognosis and that this phenomenon was more frequently observed in patients with squamous cell carcinoma than in patients with other types of carcinoma (13). In addition, the correlation between the expression of ErbB receptor family proteins and different clinical outcomes and therapeutic responses to monoclonal antibodies has also been widely studied, although the results are more heterogeneous (22). EGFR expression is frequently observed in NSCLC patients with brain metastases (23).…”
Section: Discussionmentioning
confidence: 99%
“…The same study reported that a high copy number correlated with a poor prognosis and that this phenomenon was more frequently observed in patients with squamous cell carcinoma than in patients with other types of carcinoma (13). In addition, the correlation between the expression of ErbB receptor family proteins and different clinical outcomes and therapeutic responses to monoclonal antibodies has also been widely studied, although the results are more heterogeneous (22). EGFR expression is frequently observed in NSCLC patients with brain metastases (23).…”
Section: Discussionmentioning
confidence: 99%
“…One biopsy from each site at which evaluable tissue was available was then immunostained for Ki-67 using the mib-1 monoclonal (DAKO) as described (ref. 15; Fig. 1).…”
Section: Bronchial Epithelial Ki-67 and Lung Cancermentioning
confidence: 94%
“…The Ki-67 antigen is localized to the nucleus, currently incompletely biochemically characterized, and is expressed in all phases of the cell cycle except for G 0 (13). The percentage of epithelial cells expressing Ki-67, or Ki-67 index, is progressively elevated in bronchial preneoplasias of increasing grades of severity up to and including invasive lung cancer and displays large interindividual variation, suggesting that it may reflect differences in response to carcinogens (14,15). Ki-67 index has been characterized in current and ex-smokers by Lee et al (11).…”
Section: Introductionmentioning
confidence: 99%
“…EGFR is highly expressed in a variety of human tumors, including NSCLC, and is implicated in tumor development (Grandis and Sok, 2004;Merrick et al, 2006). The overexpression of EGFR has been observed in both premalignant lesions and malignant tumors of the lung, and occurs in 40-80% of patients with NSCLC (Salomon et al, 1995;Grandis and Sok, 2004;Merrick et al, 2006).…”
Section: Egfr and Her2 Overexpressionmentioning
confidence: 99%
“…The overexpression of EGFR has been observed in both premalignant lesions and malignant tumors of the lung, and occurs in 40-80% of patients with NSCLC (Salomon et al, 1995;Grandis and Sok, 2004;Merrick et al, 2006). EGFR overexpression was suggested to result primarily from epigenetic causes, including transcriptional activation; however, gene amplification and oncogenic viruses can also have an important function (Wong et al, 1992;Rubin Grandis et al, 1996a, b;Grandis and Sok, 2004).…”
Section: Egfr and Her2 Overexpressionmentioning
confidence: 99%